The spell of the Yukon - Service, Robert W. (Robert William), 1874-1958. (New York : Putnam, 1989)
Contains selected poems reflecting the author's interest in frontier life and search for adventure.
Young Adult
Keywords: Frontier and pioneer life -- Yukon -- Poetry; Frontier and pioneer life -- Yukon -- Poetry; Klondike River Valley (Yukon) -- Poetry; Klondike River Valley (Yukon) -- Poetry